School tobacco policies and adolescent smoking in six European cities in 2013 and 2016: A school-level longitudinal study - Mélard, N (2020)
Assessment of the effectiveness of school tobacco policies (STPs) in reducing adolescent smoking remains inconclusive. Previous studies took insufficient account of different dimensions of STPs, the different views of students and staff, and policy changes over time. This study assessed how a multidimensional STP, as perceived by students and staff, was associated with adolescent smoking over time in six European cities. The SILNE and SILNE-R surveys were conducted among students (n = 18,502) and staff (n = 438) in 38 schools in 2013 and 2016. Three dimensions (comprehensiveness, enforcement, and communication) were assessed and we calculated total STP scores. Multilevel logistic regressions estimated associations of STPs with adolescent smoking on and just outside school premises and with weekly smoking. Further analyses estimated associations between 2013 and 2016 STP changes and smoking outcomes in 2016, controlling for STP and smoking prevalence in 2013. On average, there were few increases in STP scores over time. Greater STP enforcement, as perceived by students, was associated with lower odds of weekly smoking (OR:0.93, 95%CI:0.89–0.97) and of smoking on school premises (OR:0.80, 95%CI:0.72–0.90). Higher total STP scores were associated with lower odds of smoking on school premises (OR:0.76, 95%CI:0.67–0.86), but not of smoking just outside premises or smoking weekly. Greater increases in STP scores over time were associated with lower odds of smoking on school premises in 2016 (OR:0.65, 95%CI:0.47–0.89). Well-enforced STPs may help reduce adolescent smoking at school. Schools should be supported in adopting comprehensive policies that also extend to the surroundings of their premises.